"Levantamiento geológico y caracterización petrográfica, mineralógica de las rocas del intrusivo del cerro el Villonaco, ubicado en el cantón Catamayo, provincia de Loja" - Guaya Morocho, Luis Alfredo (2015)
The geology of the province of Loja was made by Kennerley, JB in 1973, and him not drew the Pluton Catamayo. In researching the metamorphic belts of Ecuador conducted by Litherland M, et al in 1994 if one takes into account the Catamayo Pluton which even dating by the Rb-Sr method. In the period 1998-2000 in the Western Cordillera work conducted by the BGS and CODIGEM occurred maps at 1: 500 000 and here's Pluton Catamayo appears and plotted. This research focuses on the study of Pluton Catamayo where petrographic and mineralogical characterization of rocks and mapping took place in this intrusive body.For this study area decide us mapping all the morphological ellipsoidal shaped body (domed) which is enclosed by the Paja Blanca and Duraznillo rivers through by a field campaign conducted in November 2014 and February 2015, a series was determined dykes and intrusive bodies of which extracted, samples for analysis and thereby determining that the rocks are mostly monzogranite type,quartzmonzonite, granodiorite, and biotite granite. Geophysical work was performed by using vertical electrical sounding (SEV) in the center of the dome but could not determine the presence of intrusive in this area, although the morphology tell us that there can be intrusive rocks in deep into this place. The mapping the Catamayo intrusive resulted in an area of 63.3 ha, the surface of this body has been affected by the chemical alteration, actually is now seen as an arcosa. An Age dated by Litherland et al, 1994 is 57 Ma which locates in the Paleocene in Thanetiano and could be correlated in depth with plutons San Lucas and Pichinal in Saraguro.